2017
DOI: 10.1055/s-0043-105489
|View full text |Cite
|
Sign up to set email alerts
|

Topical lidocaine inhibits spasm during colonoscopy: a double-blind, randomized controlled trial (with video)

Abstract: Background and study aims  Topical peppermint oil prevents intestinal spasm, but can cause rebound spasm. Lidocaine hydrochloride, a local anesthetic, may work as an antispasmodic by blocking Na + channels. The aim of this study was to investigate the effect of topical lidocaine on the inhibition of colonic spasm during colonoscopy, compared with peppermint oil. Patients and methods  A randomized, controlled double-blind trial was conducted in an academic endoscopy unit. Patients requiring endoscopic resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…This multicenter, randomized, double‐blinded controlled trial clearly showed that lidocaine dispersion during colonoscopy inhibited colorectal spasm more effectively compared with normal saline (control). To our knowledge, this is the first description of a benefit of topical lidocaine during colonoscopy, with previous research showing equivalence to topical peppermint oil …”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…This multicenter, randomized, double‐blinded controlled trial clearly showed that lidocaine dispersion during colonoscopy inhibited colorectal spasm more effectively compared with normal saline (control). To our knowledge, this is the first description of a benefit of topical lidocaine during colonoscopy, with previous research showing equivalence to topical peppermint oil …”
Section: Discussionmentioning
confidence: 69%
“…). In our previous study, median latency to spasm inhibition was 43.5 s after lidocaine application; the anesthetic effect of lidocaine is 30–45 min in mucous membranes. We therefore chose 3 min of observation as the time to assess the inhibitory effect of lidocaine.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations